VARIABLE EFFECTS OF LEUZEA CARTHAMOIDES (ASTERACEAE) EXTRACTS AND 20-HYDROXYECDYSONE ON NF-KAPPA B - Peschel, W.; Leonti, M.; Prieto, J. M. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Leuzea carthamoides (Willd.) DC. (syn. Rhaponticum carthamoides (Willd.) Iljin, Asteraceae) has adaptogenic [1], anticancer [2] and immunomodulating [3] effects. The plant –traditionally hydroethanolic extracts- and its main ecdysteroid 20-hydroxyecdysone (20-E) are increasingly offered as natural anabolics for animal and human use. Considering the central involvement of the nuclear factor NF-kappa B within the cellular immune response [4] we investigated the effect of pure 20-E and Leuzea extracts using a reporter gene luciferase based model with a transfected HeLa cell line. Cytotoxicity and proliferative effects were controlled by the MTT assay and HPLC fingerprints including 20-E determination recorded. 20-E alone showed a minor inhibitory effect between 5 and 50 ìM upon PMA or TNFá stimulation. In contrast, the stronger effects by standard inhibitors such as parthenolide or dexamethasone were attenuated. Crude hydroethanolic/methanolic herb extracts lowered (IC50 around 20ìg/ml), whereas root extracts increased NF-kappa B activation (plus 50% at 10 ì g/ml). Hydrophilic fractions both from root/herb containing 20-E and higher amounts of phenolcarbonic acids activated, whereas some of the medium polar fractions with higher portion of flavonoids and sesquiterpenlactones inhibited NF-kappa B more effectively (IC50 < 5 ì M). All effects were lowered by the transcription inhibitor dexamethasone. Spiking of the extracts with 20-E attenuated the effect of inhibitors and further increased those of activating extracts in most cases. Leuzea NF-kappa B effects are for the first time reported here. The results show that the standard marker 20-E alone is not primarily responsible, but may modify the effects exhibited by other compounds in either direction. Acknowledgements: A. Kump, Linz (AT) for material provision References: 1Slama et al. (1996) Experientia 52(7):702-6, [2] Hamburger et al. (2006) Planta Med 2006; 72: 992 [3] Kormosh et al.(2006) Phytother Res. 20(5):424-5, [4] Li Q, Verma IM. (2002) Nat Rev Immunol. 2(10):725-34